2003
DOI: 10.1023/b:ddas.0000007857.15694.15
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Symptoms in Endoscopic Reflux Esophagitis: Evaluation in 8031 Adult Subjects

Abstract: This study aimed to evaluate the correlation between symptoms and endoscopic findings in reflux esophagitis. Subjects, 8031 persons without medication for gastrointestinal disease, were briefly asked about the presence of heartburn, dysphagia, odynophagia, and acid regurgitation by associated medical staff before endoscopy for assessment of esophagitis utilizing the Los Angeles Classification. Endoscopically, 1199 (14.9%) were classified as positive reflux esophagitis, and 2223 (27.7%) had heartburn, 1522 (19.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
8
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(134 citation statements)
references
References 15 publications
2
120
8
4
Order By: Relevance
“…Today, the incidence of RE is reported to be 10%-20% in Europe and the United States [23][24][25] , and 14%-16% in Japan [26][27][28] . While the incidence of RE in Japan is considered low as compared to Europe and the United States, the incidence of RE in Japan has increased due to the westernization of the Japanese diet, the rapidly growing elderly population, and lower H pylori infection rates [26][27][28] . Parkman [5] has reported that the incidence of RE in patients was 20% (4/20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, the incidence of RE is reported to be 10%-20% in Europe and the United States [23][24][25] , and 14%-16% in Japan [26][27][28] . While the incidence of RE in Japan is considered low as compared to Europe and the United States, the incidence of RE in Japan has increased due to the westernization of the Japanese diet, the rapidly growing elderly population, and lower H pylori infection rates [26][27][28] . Parkman [5] has reported that the incidence of RE in patients was 20% (4/20).…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, with respect to the severity of RE, most patients are reported to have mild esophagitis (Grade A or B under the Los Angeles classification [26,27] . In the present study, all patients had mild esophagitis.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic abnormalities are more likely in people over 45 years of age. 33,34 Serious UGI events such as perforation or bleeding from gastric or duodenal ulcers occur in up to 2% of NSAID users, with an estimated 2000 deaths annually in the UK. 35 Bleeding and perforation are often not heralded by symptoms 36 and ulcers seen at endoscopy occur in over onequarter of people taking ibuprofen and other nonselective NSAIDs, but less commonly with COX-2 selective NSAIDs.…”
Section: Toxicity Of Nsaids Gastrointestinal Disordersmentioning
confidence: 99%
“…The majority of patients with reflux symptoms have been reported not to have endoscopically proven erosive esophagitis, even though their symptoms are severe not only in western countries but also in Japan (4)(5)(6)(7)(8)(9)(10)(11)(12). We have recently clarified that 18% of Japanese subjects who attend hospital for annual health check-ups have reflux symptoms or endoscopically proven reflux esophagitis, and that over 80% of patients with reflux symptoms do not have erosive esophagitis (13).…”
Section: Gastroesophageal Reflux Disease (Gerd) Is Characterized By Tmentioning
confidence: 99%